2020
DOI: 10.1039/c9cp06206h
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the electronic structure and charge transfer in topological insulator Bi2Te2Se and Bi2Se2Te thin films under an external electric field

Abstract: The electronic structure and charge transfer of Bi2Te2Se and Bi2Se2Te thin films are robust to an external electrical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…This is due to the fact that the valence band maximum is mainly made up of Te p-orbital, and Te deficiency results in opening up of band gap compared to pristine Te. 63 The Pisarenko plot (α ∼ p) is provided in Figure 4d, matching well with the theoretical curves with fixed effective masses in between 1.10 and 1.33 m 0 . The calculation details can be found in the Supporting Information.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This is due to the fact that the valence band maximum is mainly made up of Te p-orbital, and Te deficiency results in opening up of band gap compared to pristine Te. 63 The Pisarenko plot (α ∼ p) is provided in Figure 4d, matching well with the theoretical curves with fixed effective masses in between 1.10 and 1.33 m 0 . The calculation details can be found in the Supporting Information.…”
Section: Resultssupporting
confidence: 75%
“…The Ar and N 2 samples demonstrate nearly identical trends in PF with the highest value of ∼3.2 × 10 –3 W m –1 K –2 achieved at room temperature, comparable to the literature reports, , whereas the PF for He sample presents a similar increasing trend as its Seebeck coefficient. This is due to the fact that the valence band maximum is mainly made up of Te p-orbital, and Te deficiency results in opening up of band gap compared to pristine Te . The Pisarenko plot (α ∼ p ) is provided in Figure d, matching well with the theoretical curves with fixed effective masses in between 1.10 and 1.33 m 0 .…”
Section: Resultssupporting
confidence: 65%
“…It is known that in the case of a covalent bond, the lone-pair electrons are localized around the atoms and the electrons constituting the bonds are delocalized. Hence, the Sb–Se and Sb–Te atoms are bonded by forming covalent bonds, which is similar to the bonding nature of Bi 2 Te 2 Se and Bi 2 Se 2 Te …”
Section: Resultsmentioning
confidence: 72%
“…Hence, the Sb−Se and Sb−Te atoms are bonded by forming covalent bonds, which is similar to the bonding nature of Bi 2 Te 2 Se and Bi 2 Se 2 Te. 42 The phonon spectra of Sb 2 Se x Te 3−x are shown in Figure 2a,b, respectively. Clearly, there is no negative frequency in the spectra, which demonstrates the dynamical stability of these monolayers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The electronic structures of Bi 2 Te 2 Se and Bi 2 Se 2 Te films exhibit robustness to electric fields. 28 The topological phase transition was induced by applying hydrostatic pressure to MnBi 2 Te 4 by Pei et al 29 Mutch et al found the essential basis for the pressure-tuned ZrTe 5 topological phase transition. 30 Pressure-induced topological phase transition was also confirmed in the Dirac semimetal Cd 3 As 2 .…”
Section: Introductionmentioning
confidence: 99%